The Role of Financial and Non-Financial Compensation in Improving Employee Work Productivity at CV Galih Langgeng Jaya - Restina Restina; Sasa Dwi Andriani Saputri; Taufik Edwar; Febrianty Febrianty; Reza Hardian Pratama (International Journal of Business, Law, and Education, 2026)
Employee productivity remains a central concern for small and medium-sized enterprises because productivity determines operational continuity, cost efficiency, and the ability to achieve business targets. This study examines the effects of financial compensation and non-financial compensation on employee work productivity at CV Galih Langgeng Jaya. Using a quantitative explanatory design, data were collected through a cross-sectional questionnaire survey involving the entire population of 88 employees, selected through census sampling. The data were analyzed using partial least squares structural equation modeling (PLS-SEM) with SmartPLS. The results show that financial compensation has a positive and significant effect on work productivity (β = 0.324, t = 2.070, p = 0.038), while non-financial compensation also has a positive and significant effect (β = 0.493, t = 2.863, p = 0.004). The model explains 61.2% of the variance in employee work productivity, indicating moderate-to-substantial explanatory power. Non-financial compensation has the stronger effect, suggesting that recognition, a supportive work environment, harmonious work relationships, and career development opportunities are critical productivity drivers. However, the heterotrait-monotrait ratio indicates discriminant validity concerns between several constructs, particularly financial and non-financial compensation; therefore, the results should be interpreted with caution and future studies should refine the measurement items. The study contributes to human resource management literature by demonstrating the combined role of material and psychological rewards in enhancing employee productivity in a medium-sized enterprise context.